Improving Productivity Strategies With Failure Mode And Effect Analysis And Analytic Hierarchy Process Methods : Meningkatkan Strategi Produktivitas Dengan Metode Failure Mode and Effect Analysis Dan Analytic Hierarchy Process - Adrio, Muhammad Bayu; Wahyuni, Hana Catur (Indonesian Journal of Innovation Studies, 2023)
UD Fafa Mutiara is a business entity that produces petis as its main product. Products that are considered defective or cannot be repaired and recycled again, will be detrimental to business actors. It is estimated that in each product there are an average of 70 plastic products that are damaged, defective, or even fail, out of 5,000 plastics every month. In a day, Mrs. Ulfa can produce around 175 plastic cases which must be marketed the next day. The purpose of this research is to find out strategies that can improve the quality of UD Fafa Mutiara's petis. One way to find several problems in failure during the petition manufacturing process is known as the Failure Mode and Effect Analysis method, which is abbreviated as FMEA. This method is used to identify potential failures that may occur in the design, production process, or production results. AHP (Analytical Hierarchy Process) has a meaning as a functional hierarchy with the main input being human presumption, which has many advantages in explaining the decision-making process. The research results obtained were that the highest level of risk in the paste production process was when washing raw materials using dirty water with an RPN value of 448. The strategy of using AHP resulted in suggestions for improvements with the highest value, namely checking water with a value of 0.366. So the recommendation that can be given to UD Fafa Mutiara is to maintain the quality of the water used for washing raw materials. Highlight : Identification of potential failures: FMEA method helps identify possible failures in design and production processes. Decision-making process: AHP involves human input to explain decision-making processes effectively. Risk mitigation strategy: Maintaining water quality during raw material washing is crucial for improving product quality. Keywords - Petis; production defects; Failure Mode And Effect Analysis (FMEA); Analytic Hierarchy Process (AHP)